An Analysis of Phonological Acquisition in 22-Month-Old Children: A Case Study - Laela Fitriya; Siti Silpi Salpiah (Sumule Indonesia Publishing, 2026)
Language acquisition is a fundamental aspect of human development that begins from infancy to adulthood. This study focuses on the phonological acquisition of 22-month-old children to identify the occurrence of vowel and consonant sounds and patterns of phonological simplification at that age. This research used descriptive qualitative methods with a case study approach. Data were collected through recordings of children's natural speech, transcribed, and analysed to identify sound production, substitution, and Deletion. The results of the study show 60 occurrences of vowel phonemes, including [a], [i], [u], [e], and [o], with the vowel [a] being the most dominant. There are 40 occurrences of consonant phonemes including [k], [m], [j], [t], [b], [y], [c], [n], [w], [ᶴ], [s], [p], [d]. The point of articulation is dominated by the alveolar with a total of 14 occurrences. [k] and [d] are the most frequent phonemes, each occurring 6 times. In addition, the most frequently appearing ones are deletion rather than assimilation and palatalization.